Legally Scripted Fictions: Fathers and Fatherhood in English Language Picturebooks with Children from Refugee Backgrounds - Ekaterina Strekalova-Hughes; Nora Peterman; Kylee Lewman (CLELEjournal, 2019)
Ekaterina Strekalova-Hughes, Nora Peterman and Kylee Lewman's study uses a critical multicultural analytic lens to examine representations of fathers and fatherhood in 43 fictional picturebooks featuring children from refugee backgrounds.